Interactions I: - Tanka, Judith (McGraw-Hill, 1997)
Interactions One: A Listening/Speaking Skills Book, 3/e, is designed to help students develop effective listening strategies that will lead to language acquisition. Students apply new skills to a variety of recorded information including both life skills and academically oriented topics. Ideal for beginning to high-beginning ESOL students.